Theoretical analysis of the photonic band structure of face-centred cubic colloidal crystals - V. Yannopapas; N. Stefanou; A. Modinos (Journal of Physics: Condensed Matter, 1997)
We present a theoretical analysis of the photonic band structure of fcc colloidal crystals in relation to experimentally available transmission spectra of finite slabs of such crystals.